Accurate calculation of the eigenvalues of a new simple class of superpotentials in SUSY quantum mechanics - Fernández, Francisco Marcelo (2013)
We obtain accurate eigenvalues for two recently derived SUSY partner Hamiltonians. We improve the Rayleigh-Ritz variational method proposed by the authors and show how to apply the Riccati-Padé method to those particular partner potentials